Analisis Faktor Penentu Tingkat Partisipasi Kerja Perempuan di Provinsi Jawa Timur - Muhammad Handi Rohman; Wiwin Priana Primandhana; Wirya Wardaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Women have a strategic role in economic development, but their participation in the job market is often constrained by social, economic, and cultural factors. This study aims to analyze the factors that affect the Female Labor Force Participation Rate (TPAKP) in East Java Province during the period 2014–2023. The variables studied include the minimum wage, the average length of schooling, and the Gross Regional Domestic Product (GDP). The data used is a combined panel data between time-lapse data and cross-data from 38 districts/cities in East Java. This research method uses panel data regression analysis with the Fixed Effect Model (FEM) model. The results of the study show that the minimum wage and the average length of schooling have a positive and significant influence on TPAKP. Rising wages encourage women to enter the job market, while higher education improves skills and job opportunities. In contrast, GDP has a positive but insignificant influence, as structural barriers in the economic sector limit women's participation. The study suggests increasing the minimum wage, investing in skills education and training, as well as gender-inclusive policies to increase women's participation in the job market. This research is also expected to be a reference for further studies that can expand the understanding of TPAKP determinants in other regions.